Neodymium-iron-boron magnet, electroplated product and preparation method and application of neodymium-iron-boron magnet

The surface treatment of the neodymium iron boron magnet is carried out through sandblasting or caustic chamfering technology, controlling its roughness and removing uneven areas, solving the problem of chromatic aberration of the electroplating of the neodymium iron boron magnet, adapting to the needs of intelligent assembly, and realizing the surface color difference. Improvement and simplification of process.

CN119207985APending Publication Date: 2024-12-27NINGBO KONIT IND +4
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411150955.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing neodymium iron boron magnet plating technology is difficult to effectively solve the problem of surface chromatic aberration, especially in the intelligent assembly process, which leads to a reduction in assembly efficiency and accuracy.

Method used

The surface of the neodymium iron boron magnet is processed through the sandblasting process or the pyrolytic chamfering process, and the roughness is controlled to be between 0.7 and 0.8 μm, and the uneven surface area is removed before electroplating to ensure that the surface color difference problem after electroplating is improved.

Benefits of technology

It realizes uniform control of the surface roughness of neodymium iron boron magnets, solves the problem of surface chromatic aberration after electroplating, adapts to the needs of intelligent assembly, and simplifies the process flow, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119207985A_ABST
    Figure CN119207985A_ABST
Patent Text Reader

Abstract

The invention provides a neodymium-iron-boron magnet, an electroplated product and a preparation method and application of the neodymium-iron-boron magnet, the preparation method comprises the following steps that a neodymium-iron-boron magnet black sheet is subjected to a sand blasting process or a caustic soda chamfering process, and the neodymium-iron-boron magnet is obtained; the surface roughness Ra of the neodymium iron boron magnet is 0.7 to 0.8 [mu] m; the neodymium-iron-boron magnet black sheet is a neodymium-iron-boron magnet black sheet which is subjected to diffusion treatment in a slurry coating mode; the viscosity of the slurry is 30 to 5000 mPa * s. According to the method, the neodymium-iron-boron magnet black wafer is subjected to the sand blasting process or caustic soda chamfering process treatment, the surface roughness can be optimized, the height distribution difference of the magnet surface after acid pickling can be effectively avoided, the surface color difference after electroplating is finally reduced, operation is easy, the color difference improving effect is excellent, and the application prospect is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of neodymium iron boron magnets, and in particular to a neodymium iron boron magnet, an electroplated product, and a preparation method and use thereof. Background Art

[0002] Sintered NdFeB magnets are widely used in the 3C consumer electronics field, including mobile phones, tablets, laptops, watches, headphones and wireless charging devices, etc. They are characterized by small specifications and high performance requirements. As the demand for assembly accuracy and efficiency gradually increases, automatic identification of magnets for assembly through mechanical assistance has become a new way, and higher requirements have been placed on the appearance of NdFeB electroplated products. In the early stage, the electroplating technology of NdFeB magnets focused more on the density and corrosion resistance of the coating, but ignored the problem of color difference on the surface of the coating, which brought many inconveniences to the automated assembly process of the magnets.

[0003] CN116408358A provides a method for solving the color difference of the surface of electrogalvanized steel plates, but the solution mentions that the color difference defect of electrogalvanizing is mainly caused by the difference in diffuse reflection of light caused by the directional growth of the zinc layer and the disordered growth of the surrounding zinc layers. Therefore, a technical solution of adjusting the process at each stage to control the growth of the zinc layer is adopted, which makes the process control more complicated.

[0004] In view of this, there is an urgent need to provide a simple and feasible method to reduce the surface color difference of NdFeB magnets to meet the requirements of intelligent assembly. Summary of the invention

[0005] To solve the above technical problems, the present invention provides NdFeB magnets, electroplated products, and preparation methods and uses thereof, which solve the problem of surface color difference of NdFeB magnets, and have simple processes and are easy to produce, and can better adapt to the requirements of intelligent assembly.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a NdFeB magnet, the method comprising the following steps: subjecting a NdFeB magnet black sheet to a sandblasting process or a caustic soda chamfering process to obtain the NdFeB magnet; the surface roughness Ra of the NdFeB magnet is 0.7 to 0.8 μm; the NdFeB magnet black sheet is a NdFeB magnet black sheet that has been diffusion-treated by slurry coating; the viscosity of the slurry is 30 to 5000 mPa·s.

[0008] The inventor found that the NdFeB magnets (such as impregnation) that diffused heavy rare earths by slurry coating are prone to surface color difference after electroplating. Through further analysis, there are large height distribution differences on the surface of the color difference product, and even abnormal concave areas appear locally. The height distribution difference is not caused by uneven coating thickness, but by the large height distribution difference of the NdFeB magnets of the electroplated products. It is precisely because of this large height distribution difference that the electroplated products show surface color difference under the naked eye. Further analysis found that the NdFeB magnets that diffused heavy rare earths have local component uneven areas on the surface, and the rare earth oxide content in the uneven areas is high. This local component uneven area makes the pickling amount of the surface area inconsistent in the pickling process before electroplating, resulting in a large height distribution difference on the surface after pickling. This height distribution difference cannot be compensated or eliminated during the electroplating process, so the surface color difference of the electroplated product occurs. The inventor analyzed the reason for the high distribution difference of the NdFeB magnets diffused with heavy rare earth, and believed that it was mainly due to the presence of heavy rare earth particles in the heavy rare earth layer. During the diffusion heat treatment, the heavy rare earth particles are replaced with the Pr and Nd elements of the magnet matrix, so that the Pr and Nd elements are enriched on the surface of the magnet matrix. The heavy rare earth particle aggregation area forms a Pr and Nd element aggregation area after the diffusion heat treatment. Since the Pr and Nd elements are easy to combine with the O element to form an oxide aggregation area, after the diffusion heat treatment, there is a local component uneven area with a high rare earth oxide content on the surface. The prior art believes that the surface oxide layer can be removed by the pickling process before electroplating, but the chemical corrosion method of pickling will remove other exposed surfaces while removing the oxide layer, and the chemical corrosion of pickling is difficult to selectively remove the local uneven area on the surface. When only the pickling process is used without other methods, the inventor found that the color difference problem of the electroplated product cannot be improved.

[0009] There are two main reasons for the formation of heavy rare earth particle aggregation areas: one is that due to the low viscosity of the slurry, the heavy rare earth particles are unevenly distributed in the heavy rare earth layer coated on the surface of the substrate, and there are more heavy rare earth particles in some areas; the second reason is that in its suspension state, the heavy rare earth particles contained in the slurry are easy to agglomerate due to their small particle size (2-8μm), resulting in uneven dispersion of heavy rare earth particles in the slurry, and there are heavy rare earth particle aggregation areas in some areas of the slurry. The aggregation area will stay on the surface of the magnet substrate after being coated on the NdFeB magnet substrate and diffused. During the slurry coating process, if the slurry viscosity is high, it may lead to poor slurry stability and reduced production efficiency.

[0010] In view of the above special technical difficulties, the present invention hopes to find a solution to improve the color difference without adjusting the slurry component system, and control the roughness of the NdFeB before electroplating to 0.7-0.8μm, which can solve the surface color difference problem after electroplating. The roughness before conventional electroplating is 0.55-0.65μm. The present invention proposes to remove the surface uneven area first, so after removal, the roughness of the NdFeB before electroplating will be improved, so as to achieve the effect of improving the color difference.

[0011] In the present invention, after the NdFeB magnet black sheet is diffused by slurry coating, no other treatment is included before the "sandblasting process or caustic soda chamfering process" is performed.

[0012] The present invention further preferably adopts a sandblasting process to more accurately control the surface roughness.

[0013] Specifically, the surface roughness Ra is 0.7 to 0.8 μm, for example, 0.7 μm, 0.72 μm, 0.73 μm, 0.74 μm, 0.75 μm, 0.76 μm, 0.77 μm, 0.78 μm, 0.79 μm or 0.8 μm.

[0014] Preferably, the particle size of the particles in the slurry is in the range of 2 to 8 μm, for example, it can be 2 μm, 2.1 μm, 2.2 μm, 2.5 μm, 3 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm or 8 μm.

[0015] Preferably, the standard deviation of the surface roughness Ra between a single batch is 0.065 to 0.095, for example, it can be 0.065, 0.066, 0.067, 0.068, 0.069, 0.070, 0.072, 0.075, 0.078, 0.080, 0.082, 0.085, 0.087, 0.088, 0.089, 0.09, 0.091, 0.092, 0.093, 0.094 or 0.095, etc.

[0016] The single batch mentioned in the present invention refers to the NdFeB magnets prepared simultaneously by the method. The number of NdFeB magnets in a single batch is 5 to 100 pieces, for example, 5, 10, 15, 20, 30, 40, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 or 100 pieces prepared simultaneously.

[0017] Preferably, the extreme difference of the surface roughness Ra between a single batch is 0.15-0.35 μm, for example, it can be 0.15 μm, 0.16 μm, 0.17 μm, 0.18 μm, 0.19 μm, 0.20 μm, 0.22 μm, 0.23 μm, 0.24 μm, 0.25 μm, 0.28 μm, 0.30 μm, 0.32 μm, 0.33 μm or 035 μm, etc., preferably 0.15-0.25 μm.

[0018] Preferably, the surface roughness Ra of the iron boron magnet is 0.73-0.78 μm and the standard deviation of the surface roughness Ra between a single batch is 0.065-0.08.

[0019] Preferably, the NdFeB magnet is made of RTBM.

[0020] Wherein, the content of R is 28-30.5wt%, for example, it can be 28wt%, 28.3wt%, 28.6wt%, 28.9wt%, 29.2wt%, 29.4wt%, 29.7wt%, 30wt%, 30.3wt% or 30.5wt%, and R contains rare earth elements; the content of B is 0.85-1.05wt%, for example, it can be 0.85wt%, 0.88wt%, 0.9wt%, 0.92wt%, 0.94wt%, 0.97wt%, 0.99wt%, 1.01wt%, 1.03wt% or 1.05wt%, etc.;

[0021] The content of M is 0-3wt% and does not include 0, for example, it can be 0.1wt%, 0.5wt%, 0.8wt%, 1.1wt%, 1.4wt%, 1.8wt%, 2.1wt%, 2.4wt%, 2.7wt% or 3wt%, etc.; M includes any one of Cu, Ga, Zr, Ti, Nb, Al, Ag or W, or a combination of at least two thereof;

[0022] The content of T is the remainder after removing R, B and M, and T includes Fe and / or Co. Generally speaking, the content of T can be 65.45-70wt%, for example, it can be 65.45wt%, 66.2wt%, 66.9wt%, 67.7wt%, 68.5wt%, 69.3wt% or 70wt%, etc.

[0023] Preferably, the R includes Nd and other rare earth elements.

[0024] Preferably, the other rare earth elements include any one or a combination of at least two of Pr, La, Ce, Dy, Tb or Ho, wherein typical but non-limiting combinations are a combination of Pr and La, a combination of Ce and La, a combination of Pr and Ce, a combination of Dy and La, a combination of Pr and Dy, a combination of Ho and Dy, and a combination of Ho and Tb.

[0025] Preferably, the content of R is 28-29.5wt%, for example, it can be 28wt%, 28.2wt%, 28.4wt%, 28.5wt%, 28.7wt%, 28.9wt%, 29wt%, 29.2wt%, 29.4wt% or 29.5wt%, etc., and more preferably 28-29wt%.

[0026] Preferably, the Fe content in the T accounts for more than 97wt% of the total amount of T. Preferably, the thickness of the NdFeB magnet is ≤8mm, for example, it can be 8mm, 7mm, 6.5mm, 5mm, 4.9mm, 4.8mm, 4.5mm, 4.2mm, 4.0mm, 3.9mm, 3.8mm, 3.7mm, 3.5mm, 3.2mm or 3.0mm.

[0027] The present invention is particularly suitable for improving the color difference of small products.

[0028] Preferably, the sandblasting process includes spraying a material onto the surface of the NdFeB magnet black sheet to form a sandblasting layer.

[0029] Preferably, the spray material includes any one of corundum, silicon carbide or aluminum oxide, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of corundum and silicon carbide, a combination of aluminum oxide and silicon carbide, and a combination of corundum and aluminum oxide.

[0030] Preferably, the particle size of the corundum is 150-500 mesh, for example, it can be 150 mesh, 160 mesh, 180 mesh, 200 mesh, 220 mesh, 250 mesh, 280 mesh, 300 mesh, 334 mesh, 367 mesh, 400 mesh, 434 mesh, 467 mesh or 500 mesh.

[0031] The present invention further preferably has the grain size of the corundum in the above range, which can better control the roughness and the roughness standard deviation in a specific range.

[0032] Preferably, the injection air pressure is 0.25-0.55 MPa, for example, it can be 0.25 MPa, 0.30 MPa, 0.32 MPa, 0.35 MPa, 0.38 MPa, 0.4 MPa, 0.42 MPa, 0.43 MPa, 0.44 MPa, 0.45 MPa, 0.46 MPa, 0.47 MPa, 0.48 MPa, 0.49 MPa, 0.5 MPa, 0.52 MPa or 0.55 MPa, etc.

[0033] The present invention further preferably has the injection air pressure within the above range, which can better control the roughness and the roughness standard deviation within a specific range.

[0034] Preferably, the spraying time is 5 to 20 min, for example, it can be 5 min, 7 min, 9 min, 10 min, 12 min, 14 min, 15 min, 17 min, 19 min or 20 min.

[0035] Preferably, the inclination angle of the spraying is 30-60°, for example, it may be 30°, 34°, 37°, 40°, 44°, 47°, 50°, 54°, 57° or 60°.

[0036] The present invention further preferably has the spraying inclination angle within the above range, which can better control the roughness and the roughness standard deviation within a specific range.

[0037] Preferably, the number of the spray guns is 1 to 3, for example, 1, 2 or 3.

[0038] Preferably, a rolling ball treatment is used during the spraying process.

[0039] Preferably, the ball rolling treatment includes: mixing the black sheet and the ball rolling, and then performing sandblasting treatment.

[0040] Preferably, the mass ratio of the NdFeB magnet black sheet to the rolling ball is 3:1 to 20:1, for example, 3:1, 5:1, 8:1, 10:1, 12:1, 15:1 or 20:1.

[0041] Preferably, the rolling ball comprises any one of fluororubber balls, silicone balls, rubber balls or glass balls, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of fluororubber balls and silicone balls, a combination of rubber balls and silicone balls, a combination of fluororubber balls and rubber balls, and a combination of glass balls and silicone balls.

[0042] Preferably, the rolling speed of the rolling basket in the rolling ball treatment is 5 to 30 r / min, for example, it can be 10 r / min, 12 r / min, 13 r / min, 14 r / min, 15 r / min, 18 r / min, 20 r / min, 22 r / min, 23 r / min, 25 r / min, 28 r / min or 30 r / min, etc.

[0043] Preferably, the diameter of the rolling ball is For example, it may be 5mm, 6mm, 7mm, 8mm, 9mm, 10mm, 11mm, 12mm, 13mm, 14mm, 15mm, 18mm, 19mm or 20mm, etc.

[0044] Preferably, the sandblasting time is 5 to 30 min, for example, it can be 5 min, 6 min, 7 min, 9 min, 10 min, 12 min, 15 min, 18 min, 19 min, 20 min, 22 min, 25 min, 28 min or 30 min.

[0045] Preferably, the amount of removal in the thickness direction of the NdFeB magnet black sheet after sandblasting is 1 to 5 μm, for example, it can be 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3.0 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.5 μm, 4.8 μm or 5 μm, etc.

[0046] Preferably, the caustic soda chamfering process comprises: using a chamfering grinding fluid containing caustic soda to perform caustic soda chamfering treatment on a black sheet of a NdFeB magnet to obtain the NdFeB magnet.

[0047] Preferably, the concentration of caustic soda in the caustic soda-containing chamfering grinding liquid is 2-13 g / L, for example, 2g / L, 2.5g / L, 3g / L, 4g / L, 5g / L, 6g / L, 10g / L, 11g / L, 12g / L or 13g / L.

[0048] Preferably, the chamfering grinding fluid containing caustic soda is composed of 3-5 g / L sodium nitrite and 2-4 g / L OP emulsifier.

[0049] Wherein, sodium nitrite is 3-5 g / L, for example, it can be 3 g / L, 3.2 g / L, 3.3 g / L, 3.4 g / L, 3.5 g / L, 3.6 g / L, 3.7 g / L, 3.8 g / L, 4.0 g / L, 4.2 g / L, 4.5 g / L or 5.0 g / L, etc. OP emulsifier is 2-4 g / L, for example, it can be 2 g / L, 2.2 g / L, 2.3 g / L, 2.4 g / L, 2.5 g / L, 2.6 g / L, 2.7 g / L, 3.0 g / L, 3.2 g / L, 3.5 g / L or 4.0 g / L, etc.

[0050] Preferably, the temperature of the caustic soda chamfering treatment is 15-25°C, for example, 15°C, 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C or 25°C, etc. Preferably, the time of the caustic soda chamfering treatment is 5-10h, for example, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h or 10h, etc.

[0051] Preferably, the caustic soda chamfering step is to vibrate or tumble grind the abrasive and the NdFeB magnet black sheet in a vibrating grinder containing a chamfering grinding fluid containing caustic soda;

[0052] Preferably, the shape of the abrasive in the caustic chamfering includes any one of sphere, ellipse, triangular prism, cylinder, cone, triangular pyramid or various irregular shapes or a combination of at least two thereof;

[0053] Preferably, the material of the abrasive in the caustic soda chamfering is any one of alloy steel, Al2O3, SiC or SiO2, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of alloy steel and Al2O3, a combination of SiC and Al2O3, a combination of alloy steel and SiC, and a combination of SiO2 and SiC.

[0054] Preferably, the diffusion treatment comprises impregnation.

[0055] Preferably, the diffusion source in the diffusion treatment includes any one of heavy rare earth fluorides, heavy rare earth hydrides, heavy rare earth hydroxides or heavy rare earth alloys, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of heavy rare earth fluorides and heavy rare earth hydrides, a combination of heavy rare earth hydroxides and heavy rare earth hydrides, a combination of heavy rare earth fluorides and heavy rare earth hydroxides, and a combination of heavy rare earth alloys and heavy rare earth hydrides.

[0056] In a second aspect, the present invention provides a NdFeB electroplated product, which is prepared by using a NdFeB magnet prepared by the method for preparing a NdFeB magnet described in the first aspect, and the surface roughness Ra of the NdFeB electroplated product is 0.41 to 0.46 μm, for example, it can be 0.41 μm, 0.42 μm, 0.43 μm, 0.44 μm, 0.45 μm or 0.46 μm, etc.

[0057] Preferably, the standard deviation of the surface roughness Ra between a single batch is 0.031 to 0.039, for example, it can be 0.031, 0.032, 0.033, 0.034, 0.035, 0.036, 0.037, 0.038 or 0.039.

[0058] Preferably, the extreme difference of the surface roughness Ra of the NdFeB electroplated products between single batches is 0.08-0.14 μm, for example, it can be 0.08 μm, 0.09 μm, 0.1 μm, 0.11 μm, 0.12 μm, 0.13 μm or 0.14 μm.

[0059] Preferably, the NdFeB electroplated product comprises a NdFeB magnet and an electroplated layer disposed on the NdFeB magnet.

[0060] Preferably, the electroplating layer includes a first nickel layer, a copper layer and a second nickel layer in sequence from the NdFeB magnet outwards.

[0061] Preferably, the thickness of the first nickel layer is 2-6 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm or 6 μm.

[0062] Preferably, the copper layer has a thickness of 2-6 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm or 6 μm.

[0063] Preferably, the thickness of the second nickel layer is 3 to 7 μm, for example, it can be 3 μm, 3.2 μm, 3.4 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.2 μm, 5.5 μm, 6 μm, 6.2 μm, 6.5 μm, 6.6 μm, 6.8 μm or 7 μm.

[0064] In a third aspect, the present invention provides a method for preparing the NdFeB magnetic electroplated product described in the second aspect, the preparation method comprising: sequentially acid washing and electroplating the NdFeB magnet to obtain the NdFeB electroplated product.

[0065] Preferably, the pickling acid concentration is 0.5-5.0%, for example, it can be 0.5%, 1%, 1.2%, 1.3%, 1.5%, 2.0%, 2.2%, 2.5%, 3.0%, 3.2%, 3.5%, 4.0%, 4.2%, 4.5% or 5.0%, etc.

[0066] Preferably, the pickling temperature is 15-25°C, for example, it can be 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C or 25°C.

[0067] Preferably, the pickling acid comprises any one of nitric acid, sulfuric acid or hydrochloric acid or a combination of at least two of them, wherein a typical but non-limiting combination is a combination of nitric acid and sulfuric acid, a combination of hydrochloric acid and sulfuric acid, and a combination of nitric acid and hydrochloric acid. Preferably, the preparation method further comprises degreasing, and there is no particular limitation on degreasing, and any device and method for degreasing known to those skilled in the art can be used, and can also be adjusted according to the actual process.

[0068] Preferably, the preparation method further comprises activation, and the activation is not particularly limited, and any device and method known to those skilled in the art for activation treatment may be used, and may also be adjusted according to the actual process. The present invention has no particular limitations on the specific electroplating device and process parameters in the above process, and any device and method known to those skilled in the art for electroplating may be used, and may also be adjusted according to the actual process.

[0069] In a fifth aspect, the present invention provides a use of the NdFeB magnetic electroplated product described in the third aspect in 3C products.

[0070] The 3C products described in the present invention may be, for example, mobile phones, tablet computers, laptop computers, watches, headphones or wireless charging devices.

[0071] Compared with the prior art, the present invention has at least the following beneficial effects:

[0072] The roughness of the NdFeB magnet provided by the present invention is controlled between 0.7 and 0.8 μm, and the standard deviation of the roughness of the NdFeB magnets between a single batch is controlled between 0.065 and 0.095, thereby solving the problem of surface color difference after electroplating; moreover, the process is simple and easy to operate, easy to industrialize and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 This is a product picture of the NdFeB magnet electroplating product provided in Application Example 1 of the present invention.

[0074] Figure 2 This is an optical microscope cloud image of the NdFeB magnet electroplating product provided in Application Example 1 of the present invention.

[0075] Figure 3 This is a cross-sectional microstructure morphology of the NdFeB magnet electroplating product provided in Application Example 1 of the present invention.

[0076] Figure 4 This is a product picture of the NdFeB magnet electroplating product provided in comparative example 1 of the present invention.

[0077] Figure 5 This is an optical microscope cloud image of the NdFeB magnet electroplating product provided in Comparative Example 1 of the present invention.

[0078] Figure 6 This is a cross-sectional microstructure morphology of the NdFeB magnet electroplating product provided in comparative example 1 of the present invention.

[0079] Figure 7 This is a product picture of the NdFeB magnet electroplating product provided in comparative example 5 of the present invention. DETAILED DESCRIPTION

[0080] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0081] It should be understood that, in the description of the present invention, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more.

[0082] The specific preparation steps of the NdFeB magnet black sheet in the following examples and comparative examples are as follows:

[0083] In the smelting process, the prepared raw materials are put into a vacuum induction melting furnace, heated to 1350°C, fully melted into alloy steel liquid, poured onto a rapid cooling roller and rapidly cooled to form an alloy sheet. After secondary cooling, an alloy sheet with a thickness of 0.25 mm is obtained.

[0084] In the powder making process, the obtained alloy sheet is subjected to hydrogen embrittlement treatment and air flow mill grinding to obtain air flow milled powder with an average particle size SMD of 3.0 μm.

[0085] In the molding process, 0.2 wt% of lubricant is added to the air flow mill, and the mixture is mixed by a mixer for 120 minutes until the mixture is evenly dispersed. The mixture is pressed under nitrogen protection and an external 2T magnetic field, and a green body is obtained after cold isostatic pressing.

[0086] In the sintering process, the green body is placed in a vacuum sintering furnace, kept at 1045℃ for 300min, cooled to room temperature; then kept at 1080℃ for 300min, cooled to room temperature. The green body after sintering is further subjected to the first aging treatment at 900℃ for 240min, and the second aging treatment at 530℃ for 240min, and then cooled out of the furnace to obtain the NdFeB magnet blank.

[0087] Machining process: the NdFeB magnet blank is processed into a 4*3.5*2mm thin sheet (ie the thickness in the orientation direction is 2mm) to obtain the magnet to be diffused.

[0088] Diffusion process: The magnet to be diffused is immersed in the slurry containing heavy rare earth and then taken out and placed in a vacuum sintering furnace and then vacuumed to 10 -2 Heating was started below Pa, and the first stage heat treatment was carried out at 950℃*10h. After cooling to room temperature, it was heated again, and the second stage heat treatment was carried out at 560℃*7.5h. After cooling to room temperature, a black NdFeB magnet was obtained.

[0089] However, it does not mean that the NdFeB magnet black sheet used in the present invention must be prepared by the above method, as long as it is obtained by diffusion treatment. The component content % in the present invention represents the mass percentage by weight unless otherwise specified.

[0090] Example 1

[0091] The present embodiment provides a method for preparing a NdFeB magnet, the method comprising: spraying a spray material (corundum, with a particle size of 200 meshes) onto a NdFeB magnet black sheet (composed of 20.97% Nd, 6.84% Pr, 0.6% Co, 0.94% B, 0.3% Al, 0.2% Cu, 0.18% Ga, 2.2% Dy and 0.17% Zr, with the remainder being Fe and unavoidable impurities; the NdFeB magnet black sheet is a NdFeB magnet diffused by a slurry coating method. black flakes; the viscosity of the slurry is 1000mPa·s, and the particle size range of the slurry is 3 to 8μm), a sandblasting layer is formed on the surface to obtain the NdFeB magnet; wherein the air pressure of the spraying is 0.3MPa, and the time is 20min; the inclination angle of the spraying is 45°, and the number of spray guns is 2; a rolling ball treatment is used during the spraying process; the rolling ball treatment includes: mixing the black flakes and the rolling balls, and then sandblasting; the mass ratio of the NdFeB magnet black flakes to the rolling balls is 10:1; the rolling balls are silica gel ball; the rolling speed of the rolling basket in the rolling ball treatment is 30r / min, the sandblasting time is 20min, and the removal amount of the NdFeB magnet black sheet in the thickness direction after the sandblasting is 3μm.

[0092] Example 2

[0093] The present embodiment provides a method for preparing a NdFeB magnet, the method comprising: spraying a spray material (silicon carbide, with a particle size of 500 mesh) onto a NdFeB magnet black sheet (composed of 20% Nd, 5% Pr, 4% Ce, 1.95% Co, 1.05% B, 2.0% Ti, with the remainder being Fe and unavoidable impurities; the NdFeB magnet black sheet is a NdFeB magnet black sheet that has been diffused by a slurry coating method; the viscosity of the slurry is 4000 mPa·s, the particle size range of the slurry is 2 to 7 μm), a sandblasting layer is formed on the surface to obtain the NdFeB magnet; wherein the air pressure of the spraying is 0.25 MPa, the time is 15 min; the inclination angle of the spraying is 30°, and the number of spray guns is 3; a rolling ball treatment is used during the spraying process; the rolling ball treatment includes: mixing black sheets and rolling balls, and then sandblasting; the mass ratio of the NdFeB magnet black sheet to the rolling ball is 3:1; the rolling ball is the rolling speed of the rolling basket is 10r / min, the sandblasting time is 15min, and the amount of removal of the NdFeB magnet black sheet in the thickness direction after sandblasting is 1μm.

[0094] Example 3

[0095] The present embodiment provides a method for preparing a NdFeB magnet, the method comprising: spraying a spray material (aluminum oxide, with a particle size of 150 mesh) onto a NdFeB magnet black sheet (composed of 24% Nd, 1% La, 5% Pr, 0.5% Tb, 1.5% Co, 0.85% B, 1.0% Nb, with the remainder being Fe and unavoidable impurities; the NdFeB magnet black sheet is a NdFeB magnet black sheet that has been diffused by a slurry coating method; The viscosity of the slurry is 500mPa·s, and the particle size range of the slurry is 2-8μm), forming a sandblasting layer to obtain the NdFeB magnet; wherein the air pressure of the spraying is 0.55MPa, the time is 5min; the inclination angle of the spraying is 60°, and the number of spray guns is 1; the rolling ball treatment includes: mixing black flakes and rolling balls, and then performing sandblasting treatment; the mass ratio of the NdFeB magnet black flakes to the rolling balls is 20:1; the rolling balls are the rolling speed of the rolling basket is 20r / min, the sandblasting time is 5min, and the amount of removal of the NdFeB magnet black sheet in the thickness direction after sandblasting is 5μm.

[0096] Example 4

[0097] The present embodiment provides a method for preparing a NdFeB magnet, the method comprising: using a chamfering grinding liquid containing caustic soda (composed of 3g / L sodium nitrite and 3g / LOP emulsifier, and the concentration of caustic soda is 8g / L) to perform caustic soda chamfering treatment on a NdFeB magnet black sheet (the composition is the same as that in Example 1, and the NdFeB magnet black sheet is a NdFeB magnet black sheet that has been diffusion-treated by slurry coating; the viscosity of the slurry is 5000mPa·s, and the particle size range of the slurry is 2 to 8μm) at 18°C ​​for 8h, the caustic soda chamfering step is to roll the abrasive and the NdFeB magnet black sheet in a vibrating mill containing the chamfering grinding liquid containing caustic soda, the abrasive in the caustic soda chamfering is an elliptical alloy steel, to obtain the NdFeB magnet.

[0098] Example 5

[0099] The present embodiment provides a method for preparing a NdFeB magnet, the method comprising: using a chamfering grinding liquid containing caustic soda (composed of 3g / L sodium nitrite and 2g / L O emulsifier, the concentration of caustic soda is 12g / L) to grind a NdFeB magnet black sheet (composed of 24% Nd, 4% Pr, 0.5% Tb, 1% Co, 0.9% B, 2.5% Al, the remainder being Fe and unavoidable impurities); The NdFeB magnet black sheet is a NdFeB magnet black sheet that has been diffusion treated by slurry coating; the viscosity of the slurry is 100mPa·s, and the particle size range of the slurry is 2-6μm) and caustic soda chamfering treatment is carried out at 25°C for 5h. The caustic soda chamfering step is to vibrate the abrasive and the NdFeB magnet black sheet in a vibrating grinder containing caustic soda chamfering grinding liquid, and the abrasive in the caustic soda chamfering is cylindrical Al2O3 to obtain the NdFeB magnet.

[0100] Example 6

[0101] The present embodiment provides a method for preparing a NdFeB magnet, the method comprising: using a chamfering grinding liquid containing caustic soda (composed of 5 g / L sodium nitrite and 4 g / L O emulsifier, the concentration of caustic soda is 2 g / L) to grind a NdFeB magnet black sheet (composed of 24% Nd, 3% Pr, 1.5% Tb, 1.55% Co, 0.95% B, 1.5% Cu, 0.3% Zr, the remainder being Fe and inevitable impurities; the NdFeB magnet black sheet is a NdFeB magnet black sheet that has been diffused treated by slurry coating; the viscosity of the slurry is 3000mPa·s, and the particle size range of the slurry is 2-7μm) and caustic soda chamfering treatment is carried out at 20°C for 10h, and the caustic soda chamfering step is to roll the abrasive and the NdFeB magnet black sheet in a vibrating mill containing caustic soda chamfering grinding liquid, and the abrasive in the caustic soda chamfering is triangular prism SiC, to obtain the NdFeB magnet.

[0102] Example 7

[0103] This embodiment provides a method for preparing a NdFeB magnet. The method for preparing a NdFeB magnet is the same as that of Embodiment 1 except that the injection gas pressure is 0.15 MPa, and thus will not be described in detail.

[0104] Example 8

[0105] This embodiment provides a method for preparing a NdFeB magnet. The method for preparing a NdFeB magnet is the same as that of Embodiment 1 except that the injection gas pressure is 0.6 MPa, and thus will not be described in detail.

[0106] Example 9

[0107] This embodiment provides a NdFeB magnet. The preparation method of the NdFeB magnet is the same as that of Embodiment 1 except that the spraying inclination angle is 20°, and will not be described again.

[0108] Example 10

[0109] This embodiment provides a NdFeB magnet. The preparation method of the NdFeB magnet is the same as that of Embodiment 1 except that the spraying inclination angle is 70°, and will not be described again.

[0110] Embodiment 11

[0111] This embodiment provides a NdFeB magnet. The preparation method of the NdFeB magnet is the same as that of Embodiment 4 except that the concentration of caustic soda is higher, 15 g / L, and will not be described again.

[0112] Example 12

[0113] This embodiment provides a NdFeB magnet. The preparation method of the NdFeB magnet is the same as that of Embodiment 4 except that the concentration of caustic soda is relatively low, i.e., 1.5 g / L, and thus will not be described in detail.

[0114] Comparative Example 1

[0115] The present comparative example provides a method for preparing a NdFeB magnet, which comprises: spraying a spray material (corundum, with a particle size of 150 mesh) onto the surface of a black sheet of a NdFeB magnet raw material (the composition is the same as in Example 1, and the viscosity and particle size of the slurry are the same as in Example 1) to form a sandblasting layer to obtain the NdFeB magnet; wherein the air pressure of the spraying is 0.6 MPa, and the time is 25 min; the inclination angle of the spraying is 60°, and the number of spray guns is 1; a rolling ball treatment is used during the spraying process; the rolling ball treatment comprises: mixing the black sheet and the rolling ball, and then performing sandblasting treatment; the mass ratio of the NdFeB magnet black sheet to the rolling ball is 10:1; the rolling ball is the rolling speed of the rolling basket is 5r / min, the sandblasting time is 20min, and the amount of removal of the NdFeB magnet black sheet in the thickness direction after sandblasting is 5.5μm.

[0116] Comparative Example 2

[0117] This embodiment provides a NdFeB magnet. The preparation method of the NdFeB magnet is the same as that of Embodiment 4 except that the concentration of caustic soda is higher, 25 g / L, and will not be described again.

[0118] Comparative Example 3

[0119] This comparative example provides a method for preparing a NdFeB magnet. The method for preparing the NdFeB magnet is the same as Example 1 except that sandblasting is not performed but grinding is used to remove layers (the specific method is to grind the NdFeB magnet through a double-end grinder), and the rest is not repeated here.

[0120] Comparative Example 4

[0121] This comparative example provides a method for preparing a NdFeB magnet. The method for preparing a NdFeB magnet is the same as Example 4 except that the caustic soda chamfering treatment is not performed and is replaced by ordinary chamfering treatment (the chamfering grinding liquid does not contain caustic soda), and the rest is not repeated here.

[0122] Comparative Example 5

[0123] This comparative example provides a method for preparing a NdFeB magnet. The method for preparing a NdFeB magnet is the same as that of Example 1 except that the particle size of the corundum is 600 mesh, and thus will not be described in detail.

[0124] Comparative Example 6

[0125] This comparative example provides a method for preparing a NdFeB magnet. The method for preparing a NdFeB magnet is the same as that of Example 1 except that the particle size of the corundum is 100 mesh, and will not be described in detail herein.

[0126] Comparative Example 7

[0127] This comparative example provides a method for preparing a NdFeB magnet. The method for preparing a NdFeB magnet is the same as that of Comparative Example 4 except that the viscosity of the slurry is 6000 mPa·s, and will not be described in detail herein.

[0128] This comparative example, like comparative example 4, does not use caustic soda chamfering treatment, but only performs ordinary chamfering treatment. However, since the viscosity of the slurry is 6000 mPa·s, its viscosity is high but there is no problem of uneven material distribution. Even if caustic soda chamfering treatment is not performed, no color difference will occur, indicating that the technical problem of solving the surface color difference targeted by the present invention is a special problem that only occurs when the viscosity of the slurry is 30-5000 mPa·s.

[0129] Test method: The roughness distribution of NdFeB magnets is tested using a roughness tester. Each sample is tested along the large surface using a roughness tester. Data of 10 NdFeB magnets are collected and calculated, and the surface roughness Ra is the average value.

[0130] The test results of the above embodiments and comparative examples are shown in Table 1.

[0131] Table 1

[0132]

[0133]

[0134] Application Example 1

[0135] This application example provides a NdFeB electroplated product, which includes a NdFeB magnet and an electroplating layer arranged on the NdFeB magnet; the electroplating layer includes a first nickel layer, a copper layer and a second nickel layer in sequence from the NdFeB magnet to the outside; the thickness of the first nickel layer is 2μm; the thickness of the copper layer is 4μm; the thickness of the second nickel layer is 7μm.

[0136] The NdFeB electroplated product described in this embodiment is prepared using the NdFeB magnet provided in Example 1, and the specific preparation steps include: the NdFeB magnet is sequentially pickled with 2% nitric acid at 20°C, degreased, electroplated (including a first electroplating of a first nickel layer, a second electroplating of a copper layer, and a third electroplating of a second nickel layer) and activated to obtain the NdFeB electroplated product.

[0137] See the product picture of the NdFeB magnet electroplating product obtained in Application Example 1. Figure 1 , optical microscope cloud diagram see Figure 2 , see the cross-sectional microstructure morphology Figure 3 ,from Figures 1 to 3 It can be seen that the surface roughness uniformity of the NdFeB magnet electroplated product obtained in Application Example 1 is high, and there is no color difference under naked eye observation.

[0138] Application Example 2

[0139] This application example provides a NdFeB electroplated product, which includes a NdFeB magnet and an electroplating layer arranged on the NdFeB magnet; the electroplating layer includes a first nickel layer, a copper layer and a second nickel layer in sequence from the NdFeB magnet to the outside; the thickness of the first nickel layer is 4μm; the thickness of the copper layer is 2μm; the thickness of the second nickel layer is 3μm.

[0140] The NdFeB electroplated product described in this embodiment is prepared using the NdFeB magnet provided in Example 2, and the specific preparation steps include: the NdFeB magnet is sequentially pickled with 5% hydrochloric acid at 25°C, electroplated (including a first electroplating of a first nickel layer, a second electroplating of a copper layer, and a third electroplating of a second nickel layer) and activated to obtain the NdFeB electroplated product.

[0141] Application Example 3

[0142] This application example provides a NdFeB electroplated product, which includes a NdFeB magnet and an electroplating layer arranged on the NdFeB magnet; the electroplating layer includes a first nickel layer, a copper layer and a second nickel layer in sequence from the NdFeB magnet to the outside; the thickness of the first nickel layer is 6μm; the thickness of the copper layer is 6μm; the thickness of the second nickel layer is 3μm.

[0143] The NdFeB electroplated product described in this embodiment is prepared using the NdFeB magnet provided in Example 4, and the specific preparation steps include: the NdFeB magnet is sequentially pickled with 0.5% sulfuric acid at 15°C, degreased, electroplated (including a first electroplating of a first nickel layer, a second electroplating of a copper layer, and a third electroplating of a second nickel layer) and activated to obtain the NdFeB electroplated product.

[0144] Application Examples 4 to 12 and Comparative Application Examples 1 to 6

[0145] Application Examples 4 to 12 and Comparative Examples 1 to 6 provide a NdFeB electroplated product, which is made using the NdFeB magnets in Application Examples 3 to 12 and Comparative Examples 1 to 6, respectively. The rest is the same as Application Example 1 and will not be repeated here.

[0146] The product picture of the NdFeB magnet electroplating product obtained by using Comparative Example 1 is shown in Figure 4 , optical microscope cloud diagram see Figure 5 , see the cross-sectional microstructure morphology Figure 6 ,from Figures 4 to 6 It can be seen that the surface roughness uniformity of the NdFeB magnet electroplated product obtained by using Comparative Example 1 is very low, many pits appear, and the color difference is obvious.

[0147] The product picture of the NdFeB magnet electroplating product obtained by using Comparative Example 5 is shown in Figure 7 ,from Figure 7 It can be seen that the surface roughness uniformity of the NdFeB magnet electroplated product obtained by using Comparative Example 5 is lower than that of Application Example 1.

[0148] Test method: Use a roughness tester to test the roughness distribution of NdFeB electroplated products. Select 10 samples from each batch and use the roughness tester to test them along the large surface, and count the data of the upper and lower large surfaces.

[0149] The test results of the above application examples and application comparison examples are shown in Table 2.

[0150] Table 2

[0151]

[0152]

[0153] From Table 1 and Table 2, we can see the following points:

[0154] (1) It can be seen from the comprehensive application examples 1 to 4 that the preparation method of the NdFeB magnet provided by the present invention can control the surface roughness of the NdFeB magnet within a specific range through the sandblasting process or the caustic soda chamfering process, thereby improving the color difference problem of the electroplated product after electroplating; and the present invention further compares the remanence and coercive force data of the electroplated products obtained in application examples 1 to 3 and application examples 4 to 6, and finds that the magnetic properties of application examples 1 to 3 are better;

[0155] (2) It can be seen from the comprehensive application example 1 and application comparative examples 7 to 8 that the gas pressure of the spray in application example 1 is 0.3 MPa, compared with 0.15 MPa and 0.6 MPa in application comparative examples 7 to 8, respectively. The surface roughness Ra of the NdFeB magnet in application example 1 is 0.75 μm, and there is no color difference in the end, while the surface roughness Ra of the NdFeB magnet in application examples 7 to 8 is 0.70 μm and 0.79 μm, respectively, and there is a slight color difference on the surface of the final electroplated product. In addition, the pressure in application example 8 is too high, which may cause the surface roughness of the NdFeB magnet to be 0.75 μm and 0.79 μm, respectively. It is easy to cause the product to be blown away, resulting in serious chipping, and the yield rate will decrease. This shows that the present invention further preferably controls the pressure during sandblasting, which can better control the surface roughness of the NdFeB magnet and ultimately better avoid color difference on the surface of the electroplated product; similarly, by comparing Application Example 1 and Application Examples 9 to 10, it can be seen that if the inclination angle of the spray is too small, the product is easily blown up, resulting in increased chipping and a decrease in the yield rate; if the inclination angle of the spray is too large, the surface roughness consistency of the product is poor, the standard deviation and the range are large, and the appearance consistency is poor.

[0156] (3) It can be seen from the comprehensive application examples 4 and application examples 11-12 that the concentration of caustic soda has a great influence on the performance of the NdFeB magnet. In application example 11, the concentration of caustic soda is too high, which leads to more damage to the magnetic properties and a greater decrease in the magnetic properties. In application example 12, the roughness does not reach the preferred value, and the final product has a slight color difference. This shows that the present invention can better reduce the surface color difference while ensuring the magnetic properties of the NdFeB magnet by controlling the concentration of caustic soda within a specific range.

[0157] (4) By comparing Application Example 1, Application Example 4 and Application Comparative Examples 1 to 6, it can be seen that the color difference in Application Comparative Example 1 and Application Comparative Example 2 is relatively large, and the grinding and delamination in Application Comparative Example 3 will cause material waste. Moreover, after the magnetic property test, it is found that the coercivity of Application Comparative Example 3 decreases too much. This is because the area with the highest coercivity of the surface layer is ground away after diffusion, resulting in low coercivity of the finished product. In addition, the surface roughness of the product after grinding is very small, and ultimately the color difference of the electroplated product cannot be improved. In Application Comparative Example 5, the sandblasting efficiency is low, the cost is higher, and it is difficult to obtain the expected roughness range. In Application Comparative Example 6, the sand particles are relatively large, which will cause the surface roughness of the product to increase significantly and the uniformity is poor. The present invention controls the surface roughness of the NdFeB magnet within a specific range, so that there is no color difference on the surface of the electroplated product, and the product performance is better.

[0158] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a neodymium iron boron magnet, characterized in that: The preparation method comprises the following steps: subjecting a black sheet of NdFeB magnet to a sandblasting process or a caustic soda chamfering process to obtain the NdFeB magnet; The surface roughness Ra of the NdFeB magnet is 0.7-0.8 μm; The NdFeB magnet black sheet is a NdFeB magnet black sheet that has been diffusion-treated by slurry coating; the viscosity of the slurry is 30 to 5000 mPa·s.

2. The preparation method according to claim 1, characterized in that The standard deviation of the surface roughness Ra of the NdFeB magnets between single batches is 0.065-0.095; Preferably, the extreme difference in surface roughness Ra of the NdFeB magnets between a single batch is 0.15 to 0.35 μm, preferably 0.15 to 0.25 μm; Preferably, the surface roughness Ra of the iron-boron magnet is 0.73-0.78 μm and the standard deviation of the surface roughness Ra between a single batch is 0.065-0.08; Preferably, the composition of the NdFeB magnet is RTBM; Wherein, the content of R is 28-30.5wt%, and R is a rare earth element; The content of B is 0.85-1.05wt%; The content of M is 0 to 3 wt% and does not include 0; M includes any one of Cu, Ga, Zr, Ti, Nb, Al, Ag or W, or a combination of at least two thereof; The content of T is the remainder after removing R, B and M, and T includes Fe and / or Co; Preferably, the R includes Nd and other rare earth elements; Preferably, the other rare earth elements include any one or a combination of at least two of Pr, La, Ce, Dy, Tb or Ho; Preferably, the content of R is 28-29.5 wt%, more preferably 28-29 wt%; Preferably, the Fe content in the T accounts for more than 97 wt% of the total T amount.

3. The preparation method according to claim 1 or 2, characterized in that The thickness of the NdFeB magnet is ≤8 mm.

4. The preparation method according to claim 1, characterized in that The sandblasting process includes spraying a material onto the surface of the NdFeB magnet black sheet to form a sandblasting layer; Preferably, the spraying material includes any one of corundum, silicon carbide or aluminum oxide, or a combination of at least two thereof; Preferably, the particle size of the spray material is 150-500 mesh; Preferably, the injection pressure is 0.25-0.55 MPa; Preferably, the spraying time is 5 to 20 minutes; Preferably, the spraying angle is 30° to 60°; Preferably, the number of spray guns is 1 to 3; Preferably, a rolling ball treatment is used during the spraying process; Preferably, the ball rolling treatment includes: mixing the black sheet and the ball rolling, and then performing sandblasting treatment; Preferably, the mass ratio of the NdFeB magnet black sheet to the rolling ball is 3:1 to 20:1; Preferably, the rolling ball comprises any one of fluororubber balls, silicone balls, rubber balls or glass balls, or a combination of at least two thereof; Preferably, the rolling speed of the rolling basket in the ball rolling process is 5 to 30 r / min; Preferably, the diameter of the rolling ball is Preferably, the sandblasting time is 5 to 30 minutes; Preferably, the amount of black sheet of the NdFeB magnet removed in the thickness direction after sandblasting is 1 to 5 μm.

5. The preparation method according to claim 1, characterized in that The caustic soda chamfering process comprises: using a chamfering grinding fluid containing caustic soda to perform caustic soda chamfering treatment on a black piece of NdFeB magnet to obtain the NdFeB magnet; Preferably, the concentration of caustic soda in the chamfer grinding fluid containing caustic soda is 2 to 13 g / L; Preferably, the composition of the chamfer grinding fluid containing caustic soda is 3-5 g / L of sodium nitrite and 2-4 g / L of OP emulsifier; Preferably, the temperature of the caustic soda chamfering treatment is 15 to 25°C; Preferably, the caustic soda chamfering treatment time is 5 to 10 hours; Preferably, the caustic soda chamfering step is to vibrate or tumble grind the abrasive and the NdFeB magnet black sheet in a vibrating grinder containing a chamfering grinding fluid containing caustic soda; Preferably, the shape of the abrasive in the caustic soda chamfering includes any one of sphere, ellipse, triangular prism, cylinder, cone, triangular pyramid or various irregular shapes or a combination of at least two thereof; Preferably, the material of the abrasive in the caustic soda chamfering is any one of alloy steel, Al2O3, SiC or SiO2, or a combination of at least two of them.

6. The preparation method according to claim 1, characterized in that The preparation of the NdFeB magnet black sheet also includes: batching, smelting, hydrogen crushing, jet milling, pressing, sintering and aging before the slurry coating diffusion treatment; Preferably, the diffusion treatment comprises impregnation; Preferably, the diffusion source in the diffusion process includes any one of heavy rare earth fluoride, heavy rare earth hydride, heavy rare earth hydroxide or heavy rare earth alloy, or a combination of at least two of them.

7. A NdFeB electroplated product, characterized in that: The NdFeB electroplated product is prepared by using the NdFeB magnet prepared by the preparation method according to any one of claims 1 to 6, and the surface roughness Ra of the NdFeB electroplated product is 0.41 to 0.46 μm.

8. The NdFeB electroplated product according to claim 7, characterized in that: The range of surface roughness Ra of the NdFeB electroplated products between single batches is 0.08 to 0.14 μm; Preferably, the standard deviation of the surface roughness Ra between single batches is 0.031 to 0.039; Preferably, the NdFeB electroplated product comprises a NdFeB magnet and an electroplated layer provided on the NdFeB magnet; Preferably, the electroplating layer includes a first nickel layer, a copper layer and a second nickel layer in order from the NdFeB magnet outwards; Preferably, the thickness of the first nickel layer is 2 to 6 μm; Preferably, the thickness of the copper layer is 2 to 6 μm; Preferably, the thickness of the second nickel layer is 3-7 μm.

9. A method for preparing a NdFeB magnetic electroplated product according to claim 7 or 8, characterized in that: The preparation method comprises: sequentially pickling and electroplating a NdFeB magnet to obtain the NdFeB electroplated product; Preferably, the acid concentration of the pickling solution is 0.5-5.0%; Preferably, the pickling temperature is 15 to 25°C; Preferably, the pickling acid includes any one of nitric acid, sulfuric acid or hydrochloric acid, or a combination of at least two of them.

10. Use of the NdFeB magnetic electroplated product according to claim 7 or 8 in 3C products.

Citation Information

Patent Citations

  • Method for solving surface chromatic aberration of electro-galvanized steel sheet

    CN116408358A